The effect of routine probiotics supplementation on preterm newborn health: a regression discontinuity analysis - Bommer, Christian; Horn, Sebastian; Vollmer, Sebastian (The American journal of clinical nutrition, 2020)
Despite ongoing debate about the health impact of probiotics, rigorous evidence assessing the use of probiotics in routine preterm newborn care is lacking.We aimed to estimate the causal effect of routine probiotics supplementation on moderately preterm newborns’ anthropometric development (weight-for-age and height-for-age z scores) and risk of late-onset sepsis.This study used a regression discontinuity analysis based on hospital guidelines that recommended routine probiotics supplementation for neonates born before 34 completed weeks of gestation. Data for this study came from electronic medical records of a level III neonatal care center in Germany and were collected between 2013 and 2019. Newborns born between 30 to 38 completed weeks of gestation without severe congenital defects were eligible for inclusion. Outcomes were weight-for-age and height-for-age z scores at discharge as well as late-onset sepsis.Study participants included 1734 preterm neonates. The results showed no significant intention-to-treat effect on weight-for-age (effect: −0.033 SD; 95% CI: −0.220, 0.155), length-for-age (−0.133 SD; 95% CI: −0.380, 0.114), or late-onset sepsis probability (−1.175 percentage points; 95% CI: −6.556, 4.205). There was no evidence for significant effects of probiotics for any of the study's endpoints on those complying with the hospital guidelines (local average treatment effect).Routine treatment of moderately preterm newborns with probiotics is unlikely to improve anthropometric outcomes. Complier-level analysis suggested that this finding was not simply driven by a lack of physician compliance with hospital guidelines but by an overall absence of large health effects from the treatment itself. Moreover, overall sepsis risk was low and did not change significantly as a result of probiotics supplementation. The findings of this study therefore do not support the routine use of probiotics for improving growth or preventing late-onset sepsis in moderately preterm neonates.